2019
DOI: 10.3390/genes10100804
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Masson Pine (Pinus massoniana) under High CO2 Stress

Abstract: To explore the molecular mechanism of the response of Masson pine (Pinus massoniana), the main coniferous tree in southern China, to high CO2 stress, transcriptome sequencing was carried out to analyze the genome-wide responses of annual seedlings under different durations (0 h, 6 h, 12 h and 24 h) of high CO2 stress. The results showed that a total of 3080/1908, 3110/2115 and 2684/1483 genes were up-/down-regulated after 6 h, 12 h and 24 h of treatment, respectively, compared with control check group (CK, 0 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The lack of reference genomic data has limited Masson pine research. Transcriptome sequencing is a feasible and economical technique for generating relatively comprehensive sequencing data within a short time, and this technique has become popular in plant research 19 , 28 . Previous studies have demonstrated that the AP2 / ERF gene family is one of the most abundant transcriptional factor families in Masson pine 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of reference genomic data has limited Masson pine research. Transcriptome sequencing is a feasible and economical technique for generating relatively comprehensive sequencing data within a short time, and this technique has become popular in plant research 19 , 28 . Previous studies have demonstrated that the AP2 / ERF gene family is one of the most abundant transcriptional factor families in Masson pine 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Masson pine ( Pinus massoniana ) is an economically and ecologically important evergreen conifer in southern China and is one of the most important forest tree species 18 , 19 . It is widely used in the production of solid wood and resin 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome data for Masson pine were derived from the previously determined CO 2 stress transcriptome [ 15 ] and young shoots transcriptome (PRJNA655997). Based on the WRKY domain (PF03106), the hidden Markov model file was downloaded from the Pfam protein family database.…”
Section: Methodsmentioning
confidence: 99%
“…Air containing approximately twice the CO 2 concentration in the chamber before the experiment was aerated into the growth chamber constantly for at least 24 h. The CO 2 concentration in the chamber was monitored by an infrared CO 2 analyzer (SenseAir, Delsbo, Sweden). The seedlings were sampled after 6 h, 12 h and 24 h of treatment with the high CO 2 concentration [ 15 ]. For each treatment, leaves collected from three triangular bottles were sampled as three biological replicates for RNA-seq.…”
Section: Methodsmentioning
confidence: 99%
“…bHLH sequences of A. thaliana were downloaded from the Plant Transcription Factor database (http://planttfdb.cbi.pku.edu.cn/). Transcriptome data for Masson pine were derived from the previously determined CO 2 stress transcriptome [27], drought stress transcriptome (PRJNA595650), pine wood nematode inoculation transcriptome (PRJNA660087) and young shoots transcriptome (PRJNA655997). A Markov model (HMM) was used to screen out the bHLH gene files from the four transcriptomes by the hmmsearch program (HMMER 3.0).…”
Section: Identification Of Pmbhlh Sequencesmentioning
confidence: 99%